Peculiarities and Methods of Realisation of Mentoring Programs in US Universities - Dolinska, Nataliia (Pedagogical Discourse, 2015)
The article characterises approaches and ways of implementation of mentoring programs for young teachers in US universities. It also identifies the characteristics of mentor-mentee relationships at the level of teachers and professors staff. Duties and responsibilities of all participants of mentoring programs are outlined and chief benefits of such programs development are defined in order to facilitate the quality of professional-pedagogical training of the future teachers.